Feasibility Study of Plastic Gravity Flow Pipes Manufactured from Recycled Material - Ortiz, Efrén Wilfrido (2019)
This research presents an alternative for the manufacture of sewer pipes based on recycled material from the Quito city. The quality of the pipes manufactured with recycled high-density polyethylene (HDPE) is supported by the tests for sewer pipes: density, ring stiffness, crushing between plates, resistance to impact, transfer of pollutants from the pipe to the water that circulates through the pipeline, and cracking by environmental stress, which were made using different proportions between recycled material and virgin material.